Carrying fire: A Way forward for integral foresight - Jakonen Juha-Pekka (Elsevier Ltd, 2022)
Abstract
One of Richard Slaughter’s central innovations has been to bring the other half of reality to the field of Futures Studies. Slaughter has argued for the inner dimension of ideas, developmental levels, and mentation to be as central – if not more so – than the technical, systemic and concrete reality the field was founded upon. In this article I will present an overview of Slaughter’s central innovations that have carried the field towards a more Integral age. I will also propose a way forward for Integral Futures that is dependent on a simple heuristic model that can help simplify the complexity of Integral Theory.